Geoelectrical Characterization of Aquifer Precincts in Parts of Lapai, North Central Nigeria - MT Tsepav; SI Ibrahim; FA Bayegun (Journal of Applied Sciences and Environmental Management)
Some geoelectric characteristics of aquifer in parts of Lapai, Central Nigeria were evaluated using Wenner vertical electrical sounding (VES) method. Fifteen (15) VES points were occupied using G41 Geotron Resistivity meter with electrode spacing varying from 10m to 150m while a global positioning system (GPS) tracking device was used to locate the VES points. The 1xD Interprex interpretation software was used for the data interpretation which revealed four layers comprising the top lateritic soil, silty /clayey, weathered basement and fresh basement rocks. The resistivity of these layers varied from 4.54Ωm to 27987.60Ωm while the depth varied from 0.440m to 1079.5m. Longitudinal conductance and transverse resistance calculated from the layers’ thicknesses and resistivities varied from 0.00039Siemens to 2.05Siemens and 3.96×106 Ωm2 to 3.34×107Ωm2 respectively. The aquifer overburden protection capacity in VES 2, 5, 6,9,10 and 11 were relatively low which means the aquifer in these locations are susceptible to contaminants while in VES 15 the protective capacity is higher indicating that the aquifer is protected. Generally, all the locations could be exploited for groundwater at relatively reasonable depths. However, a greater part of the study area has low protective capacity (<1.0Siemens). The consequence of this revelation is that the area is generally unprotected as it allows for infiltration and subsequent contamination of the groundwater and hence good groundwater quality cannot be guaranteed in the area.